Development of Antioxidant-Rich Steamed Brownies Based on Kluwak, Purple Sweet Potato, and Yellow Kepok Banana - Ruly Novita Sari; Sedarnawati Yasni; Nugraha Edhi Suyatma (Eduvest - Journal of Universal Studies, 2025)
The objective of this study was to produce steamed brownies with antioxidant content using local ingredients, specifically kluwak seed powder, purple sweet potato pastes, and banana paste, which offer health benefits. The research stages include product development, treatment response determination through antioxidant capacity analysis (DPPH method), hedonic rating, and texture analysis. Determination of the optimum formulation was conducted using Design Expert 13 software. The optimum formulation was achieved with the use of 4.5% kluwak seed powder and 27.5% purple sweet potato paste from the total ingredients. Antioxidant capacity of the steamed brownies possess high antioxidant activity, but it decreased from the pre-digestion phase to the gastric and intestinal phase. This study indicated that the steamed brownies can be utilized as a functional food product with health benefits.